Proposed interior design scheme of Arowana Aquaculture Centre for Bukit Merah Aquaculture (M) Sdn. Bhd at Jalan Taman Tasik Taiping, 34000 Taiping, Perak Darul Ridzuan / Zakrul Ahmad - Ahmad, Zakrul (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect in interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for final project is to Proposed Interior Design Scheme for Arowana Aquaculture Centre at Jain Taman Tasik Taiping,34000 Taiping, Perak Darul Ridzuan. For the client is a Bukit Merah Aquaculture(M) Sdn. Bhd at 6 Tebuk Panchur, Simpang Empat,34000 Semanggol,Perak, Malaysia. It produce more than 20 types of arowana species. Before getting the design that is suitable with the client’s needs, some data analysis should be done such as the types of services offered, Bukit Merah Aquaculture product, spaces to be concluded in the proposed area,The study was performed including site selection studies, interview studies, observation studies, case studies and reseaarch with a questionnaire. Research and data collection process will be analyzed and applied in the design process to design process to design a comfortable and attractive addition to create a new image with a touch of style and design of its own.